Guided endodontic access of severe calcified tooth without incisal edge – case report - Orozco, Esteban Isaí Flores [UNESP]; Hasna, Amjad Abu [UNESP]; Andrade, Guilherme Schmitt de [UNESP]; Machado, Vinícius de Carvalho; Manhães Junior, Luiz Roberto Coutinho [UNESP]; Saavedra, Guilherme de Siqueira Ferreira Anzaloni [UNESP] (Editora Cubo, 2022)
Pulp tissue may suffer calcification because of trauma, operative procedures or carious lesions. This paper aimed to report and discuss the guided endodontic access as an alternative treatment. A 52 years old female patient had severe root canal calcification of tooth #11 associated with a radiolucent periapical lesion. Firstly, the crown and metal post and core were removed. A digital impression and cone-beam computed tomography “CBCT” scans were performed and imported to implant planning software (SimPlant Version 11; Materialise Dental, Leuven, Belgium).The guided endodontic access template was designed to allow the drill to reach a distance of 2 mm short of the apical foramen, once printed, it was tested in the mouth to evaluate its insertion and stability in the dental arch. The calcified root canal was penetrated using the access drill rotating by a low-speed hand-piece (10,000 rpm) under saline solution irrigation through advancing movements. Then, the apical foramen was negotiated with C-Pilot files #10 and #15. The working length was measured using the iPex-II apex locator. The instrumentation was carried out with Reciproc R50 and 2.5% sodium hypochlorite. One week later, a full-ceramic crown preparation was performed, and polyvinyl siloxane impression was carried out. A total of three follow-up sessions were performed after one week, one and twelve months. Bone neoformation was observed in the site of the periapical lesion and the patient had no signs or symptoms of any discomfort. Therefore, guided endodontics is indicated for severe calcified root canals.
Acesso endodôntico guiado de dente calcificado severamente sem borda incisal – relato de caso
Keywords: Access cavity; Calcified root canals; Guided endodontics